2020
DOI: 10.37624/ijert/13.6.2020.1220-1230
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Animation and Students’ Achievement in Mathematical Economics: Implications for Science Teaching

Abstract: The twenty-first-century classroom comes with changes in instructional delivery. This has demanded a paradigm shift on pedagogical practices. In the Nigerian context, literature is scarce on the impact of two-dimensional (2D) animation on students' achievement. Thus, this study explored the impact of 2D animation technique on students' achievement in mathematical contents of Economics. Non-equivalent groups quasi-experimental design was adopted for the study with a sample size of 162 senior secondary 2 Economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Ugwuanyi et al (2020a) found that animated powerpoint presentation (PPT) significantly enhanced the achievement of students in physics. Ejimonye et al (2020aEjimonye et al ( , 2020b found that the 2D animation technique had a significant effect on students' motivation and achievement in the quantitative/mathematical content of economics respectively. Ugwuanyi et al (2020b) found that digital game-based learning significantly (p < .05) improved the achievement of primary school pupils at both the post-test and follow-up measures.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ugwuanyi et al (2020a) found that animated powerpoint presentation (PPT) significantly enhanced the achievement of students in physics. Ejimonye et al (2020aEjimonye et al ( , 2020b found that the 2D animation technique had a significant effect on students' motivation and achievement in the quantitative/mathematical content of economics respectively. Ugwuanyi et al (2020b) found that digital game-based learning significantly (p < .05) improved the achievement of primary school pupils at both the post-test and follow-up measures.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…This theory is related to the present study in that computer-assisted instruction consists of both visual and audio channel which can help the students to understand mathematics and physics concepts. This theory has been successfully utilized by Ejimonye et al (2020a), Ejimonye et al (2020b), Hamzat et al (2017) and Edo (2017) to carry out similar studies.…”
Section: Theoretical Background Of the Studymentioning
confidence: 98%
“…In this study, experimental conditions were assigned randomly to intact classes. This design has been utilized by Ezema et al (2022), Adene et al (2021), Ejimonye, Onuoha, et al (2020); Ejimonye, Ugwuanyi, et al (2020), Offordile et al (2021), Njoku et al (2020), Eze et al (2021), and Ezema et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…The theory stipulates that learning is active and effective when words and pictures are integrated into the lesson. Active learning can be attained through the combination of sounds and images for a wider experience (Ejimonye et al, 2020). Students learn using different styles such as visual, aural, reading and writing but learning can be optimized when a combination of these styles is presented (Gilakjani, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%